Synopsis of acanthocerini (Hemiptera, Coreidae) from Argentina - Pall, José Luis María (2013)
Eight genera and 13 species of the tribe Acanthocerini are recorded in Argentina, i.e., Athaumastus haematicus (Sta °l), A. macer Brailovsky, A. subcarinatus (Sta °l), A. subterlineatus Bergroth, Beutelspacoris sanchezi Brailovsky, B. dilatata Casini, Camptischium clavipes (Fabricius), Crinocerus sanctus (Fabricius), Dersagrena flaviventris (Berg), D. lacerdae (Signoret), D. subfoveolata (Berg), Thlastocoris hernandezi Brailovsky and Zoreva dentipes Fabricius. Redescriptions are given for A. haematicus, A. subcarinatus and D. flaviventris with photographs of male and female genitalia of D. subfoveolata. Zoreva recorded from Argentina the first time. New locality records are given for Buenos Aires, Chaco, Formosa, Misiones, and Tucumán. © J. L. Pall, M. del C. Coscarón.